2021
DOI: 10.1021/acschemneuro.1c00057
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and Homotaurine Suppress Amyloid-β25–35 Aggregation in Synthetic Brain Membranes

Abstract: Amyloid-β (Aβ) peptides spontaneously aggregate into βand cross-β-sheets in model brain membranes. These nanometer sized can fuse into larger micrometer sized clusters and become extracellular and serve as nuclei for further plaque and fibril growth. Curcumin and homotaurine represent two different types of Aβ aggregation inhibitors. While homotaurine is a peptic antiaggregant that binds to amyloid peptides, curcumin is a nonpeptic molecule that can inhibit aggregation by changing membrane properties. By usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…An MTT assay was conducted to study the viability of INS-1 cells regulated by inhibitors. 66 15 mM caffeic acid shows a remarkable inhibitory effect on the formation of hIAPP fibrils, so it can be used as a negative control in the experiments. After incubating 15 mM hIAPP with the cells, the viability was 39.5 AE 1.0%, coincident with that reported previously.…”
Section: Interaction Study By MD Simulationsmentioning
confidence: 99%
“…An MTT assay was conducted to study the viability of INS-1 cells regulated by inhibitors. 66 15 mM caffeic acid shows a remarkable inhibitory effect on the formation of hIAPP fibrils, so it can be used as a negative control in the experiments. After incubating 15 mM hIAPP with the cells, the viability was 39.5 AE 1.0%, coincident with that reported previously.…”
Section: Interaction Study By MD Simulationsmentioning
confidence: 99%
“…This has been studied using Aβ 25–35, which is thought to be the predominant segment required for β-sheet formation and toxicity. Curcumin reduced the amount of β-sheet-rich structures formed on the membrane surface, measured by circular dichroism spectroscopy, thioflavin T fluorescence, and X-ray diffraction. , This reduction in Aβ 25–35 aggregation was attributed to curcumin’s thinning effect on the membrane, suggesting monomeric Aβ preferentially inserts into thicker and more ordered membranes . Another study measuring Aβ 1–42 aggregation using thioflavin T and immunoassays showed that curcumin-decorated liposomes reduced Aβ aggregation compared to pure liposomes .…”
Section: Introductionmentioning
confidence: 98%
“…Even at high concentrations, it is well tolerated in the human brain, where it is metabolized into 3-sulfopropanoic acid (SPA) (Figure A). TMP has been reported to prevent the formation of fibrillar forms of Aβ, reduce the Aβ-induced death rate of neuronal cell cultures, and lower the amyloid plaque deposition in the brain. Clinical trials have shown its ability to slow down the cognitive decline in patients with homozygous expression of the apolipoprotein E gene APOE4 , similarly to FDA-approved aducanumab. , TMP can act not only on Aβ, but also on other pathways that contribute to cognitive impairment in AD and other neurologic disorders. , ALZ-801 is a valine-conjugated prodrug of TMP that is currently in phase 3 of clinical trials for early stage AD patients bearing the APOE4/4 genotype (NCT04770220). , Preliminary in vitro and in silico studies suggested that both TMP and SPA can lock the Aβ peptides in monomeric conformations that are less prone to oligomerization, thus inhibiting the first step in the pathological pathway of Aβ. However, these studies do not provide sufficient insights to fully explain the mechanism of action of these molecules on Aβ. At the moment, it is still unclear whether TMP or its metabolite SPA can exert a stronger biological effect, and this was one of our motivations to carry out this study.…”
Section: Introductionmentioning
confidence: 99%